Assessment of Pharmacotherapy of Myocardial Infarction Patients at Fauji Foundation Hospital, Peshawar - Haris Khan, Muhammad Amin, Sheraz Khan, Muhammad Ibrahim Khan, Hazrat Abbas, Shaheer Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Observation of drug-drug interaction in myocardial infarction at Fauji Foundation Hospital, Peshawar Methodology: A cross-sectional descriptive study was conducted from May 1, 2022 to July 30, 2022 at Fauji Foundation Hospital, Peshawar. The sample size was 45. The study population was patients admitted to the cardiology unit with a diagnosis of myocardial infarction. A purposive sampling technique was used in the assessment and interview of the patient. Patients suffering from myocardial infarction admitted to hospital during the above-mentioned period were included in this work. Results: All patients diagnosed with myocardial infarction had major complaints of chest pain and vomiting. There was nausea and sweating in four out of ten cases (80%). Less than half were presented with SOB (shortness of breath) and body aches. Almost two-thirds (60%) of the patients used Glimepiride in the past. Amlodipine and insulin were used by 40% of patients (n =18), while Gibenclamide and metformin were used by 20% of patients (n =9). All the patients had used tablets in the past. Injectables and capsules were used in proportions of 28 and 24 percent, respectively. Practical implication: This study will provide information to the physician that the major problem with polypharmacy in hospitals is drug-drug interactions. Conclusion: The study revealed the majority of patients with MI presented with chest pain. The researcher found the main problem with polypharmacy in hospitals is drug-drug interactions. Also, there is a lack of patient counseling, which leads to irrational use of medication. Keywords: pharmacotherapy; myocardial infarction; polypharmacy; drug-drug interaction